Breast and ovarian cancer referrals to the ACT Genetic Service: are we meeting guidelines?. Issue 3 (March 2017) - Aitken, Lucy; Warwick, Linda; Davis, Alison
Abstract : Background: The ACT Genetic Service at The Canberra Hospital evaluates the genetic risk of individuals for inherited diseases, and provides counselling and genetic testing where appropriate. Aim: To evaluate the current referral practice for patients with a personal and/or family history of breast and/or ovarian cancer, and to assess whether these referrals are made according to eviQ cancer referral guidelines. Methods: A retrospective clinical audit of patients seen by the ACT Genetic Service for evaluation of genetic risk of breast and/or ovarian cancer between 1 January 2013 and 30 June 2015. Statistical analysis included Chi‐squared and Poisson distribution tests. Results: Of the 711 patients referred during the 30‐month period, 671 were seen by the service. The number of patients seen increased steadily over the time period, as did waiting times. The majority of referrals were made by general practitioners (403/711; 57%) and oncologists (172/711; 24%). Of note, 300 of 711 (42%) of all referrals made to the service during this time period did not meet eviQ referral guidelines. Patients who met guidelines for referral were more likely both to be offered genetic testing and to have a positive result. Conclusion: Demand on the ACT Genetic Service increased over the time period assessed. As a significant proportion of patients did not meet eviQ cancer referral guidelines, it is worth reviewing the referral process in order to optimise utility of this limited resource.